Society 5.0: Human-Centered Society Challenges and Solutions - Kravets, Alla G.; Bolshakov, Alexander A.; Shcherbakov, Maxim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book focuses on open issues of Society 5.0, a new paradigm of a society that balances a human-centred approach and technologies based on cyber-physical systems and artificial intelligence. The book contains results of how intelligent or cyber-physical systems help to improve the quality of life in society despite new challenges. Discusses implemented breakthrough systems, models, programs, and methods that cover the following topics: biomedicine and healthcare, innovations in socio-economic systems, intelligent energetics, advances in transport systems, human-centric technologies. These approaches help to improve human society using cyber-physical systems in a dramatically changing environment. The target audience of the book are practitioners, enterprises representatives, scientists, PhD and Master students who perform scientific research on the application of cyber-physical systems towards Society 5.0.
Society 5.0: Biomedicine and Healthcare -- Society 5.0: Innovations in Socio-Economic Systems -- Society 5.0: Intelligent Energetics -- Society 5.0: Advances in Transport Systems -- Society 5.0: Human-centric technologies.
Keywords: Cooperating objects (Computer systems).; Computational intelligence; Engineering -- Data processing; Cyber-Physical Systems; Computational Intelligence; Data Engineering; Human-computer interaction; Cooperating objects (Computer systems); Artificial intelligence -- Social aspects